Effect of safflower yellow on platelet activating factor mediated platelet activation in patients with coronary heart disease - Huang, Damin; Lu, Yingmin; Luo, Xiaohan; Shi, Laixin; Zhang, Jinchun; Shen, Junxian; Bao, Minmin; Song, Lei; Wei, Caiwen; Li, Hongsong; et al. (Bangladesh Journal of Pharmacology, 2012)
The platelet aggregation and 5-HT release by washed platelet from coronary heart disease patients following platelet activating factor (PAF) treatment were detected by turbidimetry and O-phthalaldehyde assay. The free calcium concentration in the platelets was measured with the fura-2/AM probe fluorescent technique. Results showed safflower yellow could inhibit the PAF induced washed platelet aggregation and 5-HT release, which were in a safflor-yellow-dose dependent manner. When the PAF was 2.0×10-9 mol/L, the inhibition rate of platelet aggregation was 26.2%, 41.3%, 58.1%, 81.2%, and the inhibition rate of 5-HT release was 3.7%, 11.9%, 29.9% and 54.4% after treatment with safflower yellow at 0.21, 0.42, 0.85 and 1.69 g/L, respectively. The study concludes safflower yellow can inhibit the PAF induced platelet aggregation, 5-HT release by platelets and elevation of free calcium in platelets.